2012
DOI: 10.3346/jkms.2012.27.4.337
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Controlled Protocol for Three Months Steroid Withdrawal with Tacrolimus, Basiliximab, and Mycophenolate Mofetil in Renal Transplant Recipients

Abstract: During the past few years, new immunosuppressants, such as tacrolimus, mycophenolate mofetil (MMF) and basiliximab, have been shown to successfully decrease the incidence of acute rejection, possibly acting as potent substrates for safe steroid withdrawal. Therefore, clinical outcome of 3 months steroid withdrawal, while using the above immunosuppressants, was analyzed. Clinical trial registry No. was NCT 01550445. Thirty de novo renal transplant recipients were enrolled, and prednisolone was slowly withdrawn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Two RCTslasting 1 y and comparing steroid withdrawal at 3 mo to steroid maintenance-found no significant difference in the rates of AR and GL, or in cardiovascular outcomes, new onset diabetes mellitus (NODM), or survival. 10,11 Two other 1-y RCTs compared early (7-day) steroid withdrawal to steroid maintenance, and came to the same conclusion. 12,13 A recent 5-y trial found no difference among African American patients in the rates of AR and NODM between steroid maintenance and rapidwithdrawal regimens.…”
mentioning
confidence: 70%
“…Two RCTslasting 1 y and comparing steroid withdrawal at 3 mo to steroid maintenance-found no significant difference in the rates of AR and GL, or in cardiovascular outcomes, new onset diabetes mellitus (NODM), or survival. 10,11 Two other 1-y RCTs compared early (7-day) steroid withdrawal to steroid maintenance, and came to the same conclusion. 12,13 A recent 5-y trial found no difference among African American patients in the rates of AR and NODM between steroid maintenance and rapidwithdrawal regimens.…”
mentioning
confidence: 70%